Geant4 simulation study of β-γ coincidence detector for 41Ar measurement - FENG Yajie; ZHANG Ruiqin; NIU Yazhou; LI Qi; TONG Lili; WANG Shilian; ZHAO Yungang; FAN Yuanqing; ZHANG Xinjun (He jishu)
Background41Ar is one of the main radionuclides released into the environment by the operation of reactors and accelerators. The measurement of 41Ar activity concentration is of great significance for ensuring public health. In the field of radioactive gas measurement, the β-γ coincidence method is widely used because it can significantly reduce the background and improve the sensitivity of the detector. However, there is currently little research on β-γ coincidence detectors for 41Ar measurements in literature.PurposeThis study aims to optimize the β-γ coincidence detector composed of plastic scintillator (PS) and CsI(Tl) scintillator to realize high sensitivity measurement of 41Ar.MethodsAn optimization method of detector structure based on minimum detectable concentration (MDC) was proposed. The optimization process of the detector was realized based on Geant4 simulation. Firstly, the penetration percentage of β-rays depositing energy into CsI(Tl) through different thicknesses of BC404 and 0.5 mm aluminum film was simulated. Secondly, the variation of full-energy peak efficiency of 1 293.6 keV γ-ray in CsI(Tl) scintillator with different thicknesses of CsI(Tl) was simulated. Thirdly, simulating with different gas chamber volume, the comprehensive effects of β-rays detection efficiency, γ-ray full-energy peak efficiency, gas chamber volume and sampling time on MDC were analyzed with the assumption that the sampling time of argon was proportional to the volume of the detector's gas chamber. Finally, the influence of measurement time on MDC under different background counting rates was analyzed.ResultsSimulation results show that the penetration percentage of β-rays emitted from the decay of 41Ar is about 0.78% when the thickness of BC404 is 3 mm. The γ-ray full-energy peak efficiency increases with the increase of CsI(Tl) scintillator thickness. With the argon sampling rate of 600 mL∙h-1, the optimal detector size parameters that minimize MDC are completely determined. When the background count rate is 1×10-3~1 s-1, the recommended measurement time for 41Ar is about 200 min. The MDC of the optimized β-γ coincidence detector for 41Ar measurement is about 1.7 Bq∙m-3 under the condition of measurement time of 200 min, background count rate of 5×10-3 s-1 and sample cooling time of 30 min.ConclusionsThe detector structure optimization method used for β-γ coincidence detectors in this study can be applied to the structural design of other radioactive gas detectors, and the impact of detector structure on background counting rate needs to be considered in further enhancement study.